UX Requirements Matters: Guidelines to Support Software Teams on the Writing of Acceptance Criteria - Martinelli, Suéllen; Nascimento, Nicolas; Souza, Jonathan; Sales, Afonso; Zaina, Luciana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
User Stories (USs) are artifacts that define requirements in agile software development and that are usually complemented by Acceptance Criteria (AC) which provide details about what should be implemented. These details often attempt to integrate User Experience (UX) requirements to their descriptions. This paper aims to introduce a set of guidelines that supports software teams to write UX requirements during the elaboration of AC. The guidelines are separated into Interaction Design (ID) and Visual Elements (VE). We conducted a case study with 10 agile teams that develop mobile applications that used the guidelines during a sprint. After that, we carried out a qualitative analysis of the UX requirements described in the USs/AC to evaluate the usage of the guidelines. We analyzed the guidelines’ acceptance regarding usefulness and ease of use based on feedback from the teams. We analyzed 242 AC and identified that 99 AC had UX requirements related to ID and 87 to VE. We identified that only 7 developers, spread over four teams, reported negative feedback about the guidelines. We conclude that teams were helped by the guidelines that respectively address details about the user’s interaction with the product, as well as the definition of the most adequate visual elements to enable this interaction.